First occurrence of bidens mottle virus in Brazil: biological and molecular characterization of isolates infecting Zinnia sp. and Bidens pilosa - Favara, Gabriel Madoglio; Ferro, Camila Geovana; Bello, Vinicius Henrique; Oliveira, Felipe Franco de; Kraide, Heron Delgado; Ribeiro-Junior, Marcos Roberto [UNESP]; Krause-Sakate, Renate [UNESP]; Kitajima, Elliot Watanabe; Rezende, Jorge Alberto Marques (FapUNIFESP (SciELO), 2024)
Zinnia sp. and hairy beggartick (Bidens pilosa) plants exhibiting symptoms of possible virus infection were found in the municipality of Santa Bárbara d’Oeste, São Paulo State, Brazil. Flexuous filamentous particles and cytoplasmatic inclusions typical of potyvirus infection were observed by transmission electron microscopy, respectively, in leaf extracts and cells of symptomatic leaves. Infection of both plants with bidens mottle virus (BiMoV) was confirmed by RT-PCR using potyvirus universal primers, followed by nucleotide sequencing of the amplicons. The nearly complete genome sequence of the Brazilian isolate, named BiMoV-BR, is 9700 nucleotides long and shares 95.6 % identity with the corresponding nucleotide sequence of a BiMoV isolate from the United States. BiMoV-BR was mechanically transmitted and caused systemic infection on plants of Zinnia sp., hairy beggarstick, sunflower (Helianthus annuus), and lettuce (Lactuca sativa). Myzus persicae transmitted the virus to Zinnia sp. plants with efficacy of 8 % and 42 %, using one and ten aphids per plant, respectively. This is the first detection of BiMoV in Brazil. Further studies are necessary to evaluate the distribution of this potyvirus in the country.
Keywords: BiMoV; high-throughput sequencing; Potyvirus